Examining the Integration of ICT into Teaching and Learning: A Study of Colleges of Education in the Volta Region - Asianoa, Rosemond; Kuupille, Fredrick; Segbefia, Samuel Kwabla; Asenso, James Adjabeng (Integrated Journal for Research in Arts and Humanities, 2022)
The provision of education to citizens is a requirement for economic and social development, and globalization and the transition to a knowledge-based economy require that existing educational institutions produce individuals who can convert information into knowledge and apply that knowledge in a dynamic, cross-cultural setting. The successful integration of ICT into the learning environment requires instructors to be able to design learning in creative ways, integrate technology with a pedagogy successfully, develop socially engaged learning settings, and encourage cooperative involvement. Students and student teachers frequently have more knowledge and experience with ICT than instructors and teacher educators, and for many people, this demands a different set of abilities than those they now possess. The desire for online learning to satisfy the needs of Ghana's universities' expanding student population remains a worry despite the ongoing discussions and difficulties that higher education faces. Many Ghanaian stakeholders now have a keen interest in the country's level of science and technology. This study's goal was to look at how ICT was used in teaching and learning, with a particular emphasis on the College of Education in the Volta Region. The specific goals of the study were to find out how much ICT was used in teaching and learning in colleges of education in the Volta Region, to find out what factors affected ICT use in teaching and learning in colleges of education in the Volta Region, and to find out what stopped ICT from being used in those institutions. Two theories, notably the Social Constructivist Theory and the Diffusion of Innovation Theory, served as the foundation for the study. The paper employed a desk study review methodology to examine pertinent empirical literature and identify key themes. The results showed that ICT can be utilized as a tool to support transformative, learner-centered faculty development; nevertheless, researchers caution that this approach may be challenging because teachers must contend with both the new technology problems and the learner-centered paradigm. According to the study's findings, ICT can match the current educational system with the knowledge-based, information-rich society by giving it access to high-end tools, approaches, and methodologies. To use ICT in the process of teaching and learning, the study thus advises colleges in the Volta area to build strategies to identify strengths and weaknesses of various technology resources with the aim of adopting ICT in the process of teaching and learning.